The Influence of Work Motivation and Employee Competence on Employee Performance: Study On Creative Industry Companies in The Technology Sector - Apriliyandi, Rizki; Roslina, Nita Yura; Rusjiana, Jimmy; Meliawati, Resna; Marfianti, Fitri; Damanik, Firmansyah (Journal of Economics, Management, and Entrepreneurship, 2024)
This study examines the impact of Work Motivation and Employee Competence on Employee Performance within technology sector organizations in the creative industry. Job motivation and employee competency were the primary factors significantly influencing job effectiveness and efficiency. This study employs a quantitative methodology via a survey approach, wherein data is gathered via questionnaires administered to employees. The analytical results indicate that Work Motivation and Employee Competence strongly influence Employee Performance. Work motivation exerts a more significant influence than employee competence, yet both positively enhance performance.This study revealed a strong correlation between Work Motivation and Employee Competence, indicating that highly motivated individuals typically exhibit superior competence. This discovery underscores the need to focus on these two elements to enhance employee performance. This study suggests that factors beyond Work Motivation and Employee Competence also influence Employee Performance, warranting more investigation to discover these elements.The study's findings suggest that management in the technology sector creative organizations should prioritize enhancing employee work motivation by offering rewards and incentives and fostering a supportive work environment. Moreover, initiatives to enhance Employee Competence via training and professional development are crucial to guarantee that employees possess sufficient skills and knowledge. Consequently, employee performance may be markedly enhanced. This study offers insights for firms to develop more successful human resource management strategies, emphasizing motivation and competence as crucial elements for achieving optimal performance.